2007
DOI: 10.1080/07420520601139755
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Occurrence of Pulmonary Embolism: Analysis of the Database of the Emilia‐Romagna Region, Italy

Abstract: Seasonal variation in the occurrence of cardiovascular and cerebrovascular events, including pulmonary embolism (PE), has been reported; however, recent large-scale, population-based studies conducted in the United States did not confirm such seasonality. The aim of this large-scale population study was to determine whether a temporal pattern in the occurrence of PE exists. The analysis considered all consecutive cases of PE in the database of all hospital admissions of the Emilia Romagna region in Italy at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 62 publications
4
64
1
Order By: Relevance
“…We also surveyed the incidence of pulmonary embolism, a fatal complication of DVT, was also lower in summer half than the winter half at the same time in Zhou's report (59.1% in winter half). The result was accorded with previously reported by Fink and Gallerani [10,11] . Second, Zhou et al found that the DVT incidence peaked in March in Hubei Province, China.…”
Section: Hypothesissupporting
confidence: 95%
“…We also surveyed the incidence of pulmonary embolism, a fatal complication of DVT, was also lower in summer half than the winter half at the same time in Zhou's report (59.1% in winter half). The result was accorded with previously reported by Fink and Gallerani [10,11] . Second, Zhou et al found that the DVT incidence peaked in March in Hubei Province, China.…”
Section: Hypothesissupporting
confidence: 95%
“…have focused primarily on 24 h and/or seasonal variation in cardiovascular morbidity and mortality (Gallerani et al, 2007;Manfredini et al, 2005aManfredini et al, , 2005bMehta et al, 2005) and annual patterns in common communicable infectious diseases that primarily affect young school children (Shah et al, 2006). This study examined the cyclic variation and time trends in the incidence of chlamydia, gonorrhea, and syphilis in recent years using the SAS Proc MIXED general linear model.…”
Section: Recent Epidemiology Studies Published In Chronobiology Intermentioning
confidence: 99%
“…All of the meteorological parameters have complex biological effects on human bodies (Braga et al 2002;Cagle and Hubbard 2005;Gyllerup 2000); therefore, there is an increasing interest in the connection between environmental-meteorological factors and vascular disease's morbidity and mortality. Reports in the literature suggest that weather changes may play a role in venous thrombotic disease (Stein et al 2004;Boulay et al 2001) and in the occurrence of PE as well (Öztuna et al 2008;Gallerani et al 2007). …”
mentioning
confidence: 97%